Improving the Penal Institution for Several Crimes in the Criminal Law of Uzbekistan - Qunduz Rozimova (Genius Journals, 2022)
This article analyzes some features of improving the penal institution for criminal offenses in Uzbekistan's criminal law in the context of combating corruption. In particular, the theoretical views of scientists on the commission of several crimes and recidivism are studied. At the end of the article, the author developed proposals to improve criminal law in this area.
Keywords: Corruption; Criminal Law; Punishment; Multiple Crimes